Al-Qur’an dan Teori Pengetahuan: Melacak Formula Epistemologi dalam Al-Qur’an dan Implikasinya Terhadap Pendidikan Islam - Eko Sumadi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: The government has forced the Indonesian National Qualifications Framework (KKNI) into the curriculum of every level of education, from basic education to higher education. Thus, the influence of the demands of society, political maps, social and economic conditions is far more dominant in determining the direction of education in Indonesia than the system of public trust that accumulates in its philosophical view. Important philosophical beliefs as a counterweight and also determine the direction of the pace of education, so that educational institutions do not necessarily only function as producers of labor. On the awareness of the importance of the philosophical dimension in determining the direction of education (Islam), there are still parties (Muslims) who are allergic to even consider sinful, in touch with philosophy with all its rules. This article will answer the question; How is the construction of epistemology of knowledge according to the Qur'an and what are the implications of the epistemology for Islamic education? Kata Kunci: Epistemologi, Pendidikan Islam, dan Al-Qur’an